2007
DOI: 10.1541/ieejsmas.127.187
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of Smooth Si Mold for Hot Embossing Process

Abstract: In this paper, we propose a fabrication and characterization of silicon mold for PMMA hot embossing process. Silicon molds were fabricated from silicon wafer with thickness of 500µm. First, DRIE technique was performed after optimized etching time and deposition (passivation) time to obtain a depth of 30µm with positive tapered sidewall of 1°. This is very important for de-molding process while hot embossing. Second, in order to reduce scalloping steps on the sidewall after DRIE, silicon molds were soaked in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Hiroaki et al demonstrated that introducing O 2 plasma to the DRIE process results in smoother sidewalls, and Mukherjee et al also achieved 7 nm surface roughness on sidewalls introducing O 2 into the DRIE chamber . Pham et al used tetramethylammonium hydroxide (TMAH) at 80 °C to achieve a feature size of 2 µm and smooth sidewalls . Smooth sidewalls/edges are critical for applications involving electronic transport as the rough edges would scatter electrons and reduce overall current.…”
Section: Summary Of Key Deep Etching Work Over the Past Few Decadesmentioning
confidence: 99%
“…Hiroaki et al demonstrated that introducing O 2 plasma to the DRIE process results in smoother sidewalls, and Mukherjee et al also achieved 7 nm surface roughness on sidewalls introducing O 2 into the DRIE chamber . Pham et al used tetramethylammonium hydroxide (TMAH) at 80 °C to achieve a feature size of 2 µm and smooth sidewalls . Smooth sidewalls/edges are critical for applications involving electronic transport as the rough edges would scatter electrons and reduce overall current.…”
Section: Summary Of Key Deep Etching Work Over the Past Few Decadesmentioning
confidence: 99%
“…ICP-RIE conditions were investigated carefully to guarantee the positive taper on the sidewall of the mold. 6 Last, a lubricating agent ͑3M Novec Electronic Coating EGC-1720͒ for easier demolding was applied to the Si mold before going to the embossing process. Figure 4 shows the fabricated silicon mold ͑upper image͒ and a close-up image of the comb fingers ͑lower image͒.…”
Section: Mold Fabricationmentioning
confidence: 99%
“…Next, photoresist is removed and the second ICP-RIE process is performed (with the etching mask is SiO2) to a depth of 70 ptm, and the patterns of the movable part are created (figure 4d). ICP-RIE conditions was investigated carefully to guarantee the positive taper of the side wall of the mold [6]. Finally lubricating agent for easier de-molding is applied to the Si mold before perfroming embossing process.…”
Section: Fabrication Of Two-step Si Moldmentioning
confidence: 99%